2015
DOI: 10.1097/j.pain.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind, placebo-, and active-controlled study of T-type calcium channel blocker ABT-639 in patients with diabetic peripheral neuropathic pain

Abstract: Supplemental Digital Content is Available in the Text.Treatment with ABT-639 100 mg for 6 weeks did not significantly reduce pain in patients with diabetic peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…However, subsequent clinical trials of ABT-639 with human volunteers showed no effect in an acute intradermal capsaicin pain model in which pregabalin was effective 192 . Similarly, ABT-639 did not reduce pain in patients with diabetic neuropathy 193 . Other Cav3.2 inhibitors have been described to be effective in pain models, including a rat model of pain from irritable bowel syndrome.…”
Section: Ion Channels As Drug Targetsmentioning
confidence: 89%
“…However, subsequent clinical trials of ABT-639 with human volunteers showed no effect in an acute intradermal capsaicin pain model in which pregabalin was effective 192 . Similarly, ABT-639 did not reduce pain in patients with diabetic neuropathy 193 . Other Cav3.2 inhibitors have been described to be effective in pain models, including a rat model of pain from irritable bowel syndrome.…”
Section: Ion Channels As Drug Targetsmentioning
confidence: 89%
“…Furthermore, we are aware of at least two T-type channel blockers that are being tested in humans for safety and efficacy in pain: Z944 (Lee, 2014) and 4,6,7,8,pyrazine-2-carbonyl]-4-chloro-2-fluoro-N-(2-fluorophenyl) benzenesulfonamide] (Ziegler et al, 2015). This underscores the importance of T-type calcium channels (particularly Ca V 3.2) in the primary afferent pain pathway.…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…; Ziegler et al . ). Here, we conducted a comprehensive characterization of T‐channel function in the mouse and rat subiculum by combining whole‐cell patch‐clamp electrophysiology with pharmacological, molecular and genetic tools that selectively target T‐channels.…”
Section: Introductionmentioning
confidence: 99%